Synergistic and antibiofilm potential of Curcuma aromatica derived silver nanoparticles in combination with antibiotics against multidrug-resistant pathogens - Tawre, Madhumita S.; Shiledar, Aishwarya; Satpute, Surekha K.; Ahire, Kedar; Ghosh, Sougata; Pardesi, Karishma (Frontiers in Chemistry, 2022)
Hospital acquired infections caused due to ESKAPE pathogens pose a challenge for treatment due to their growing antimicrobial resistance. Curcuma aromatica (CA) is traditionally known for its antibacterial, wound healing and anti-inflammatory properties. The present study highlights the biogenic synthesis of silver nanoparticles (CAAgNPs) capped and stabilized by the compounds from CA rhizome extract, also further demonstrating their antibacterial, antibiofilm and synergistic effects against multidrug-resistant (MDR) pathogens. CAAgNPs were synthesized using aqueous rhizome extract of CA (5 mg/ml) and AgNO3 (0.8 mM) incubated at 60°C up to 144 h. UV-vis spectroscopy, field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD) revealed CAAgNPs with characteristic peak at 430 nm, 13 ± 5 nm size of spherical shape, showing presence of silver and crystalline nature, respectively. Dynamic light scattering (DLS) and zeta potential confirmed their monodispersed nature with average diameter of 77.88 ± 48.60 nm and stability. Fourier transform infrared spectroscopic (FTIR) analysis demonstrated the presence of phenolic -OH and carbonyl groups possibly involved in the reduction and stabilization of CAAgNPs. The minimum inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs) and minimum biofilm inhibitory concentrations (MBICs) of CAAgNPs against Pseudomonas aeruginosa, NCIM 5029 and PAW1, and, Staphylococcus aureus, NCIM 5021 and S8 were in range from 8 to 128 μg/ml. Almost 50% disruption of pre-formed biofilms at concentrations 8–1,024 μg/ml was observed. Fluorescence microscopy and FESEM analysis confirmed cell death and disruption of pre-formed biofilms of P. aeruginosa PAW1 and S. aureus S8. Checkerboard assay demonstrated the synergistic effect of CAAgNPs (0.125–4 μg/ml) in combination with various antibiotics (0.063–1,024 μg/ml) against planktonic and biofilm forms of P. aeruginosa PAW1. The study confirms the antibacterial and antibiofilm activity of CAAgNPs alone and in combination with antibiotics against MDR pathogens, thus, reducing the dose as well as toxicity of both. CAAgNPs have the potential to be used in wound dressings and ointments, and to improve the performances of medical devices and surgical implants. In vivo toxicity of CAAgNPs however needs to be tested further using mice models.